2000
DOI: 10.1128/iai.68.6.3067-3073.2000
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica Serovar Typhi Uses Type IVB Pili To Enter Human Intestinal Epithelial Cells

Abstract: DNA sequencing upstream of the Salmonella enterica serovar Typhi pilV and rci genes previously identified in the ca. 118-kb major pathogenicity island (X.-L. Zhang, C. Morris, and J. Hackett, Gene 202:139-146, 1997) identified a further 10 pil genes apparently forming a pil operon. The product of the pilS gene, prePilS protein (a putative type IVB structural prepilin) was purified, and an anti-prePilS antiserum was raised in mice. Mutants of serovar Typhi either lacking the whole pil operon or with an insertio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
155
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(160 citation statements)
references
References 18 publications
3
155
1
1
Order By: Relevance
“…Another important island is the SPI-7 which is responsible for the production of the Vi polysaccharide capsule (20). This island is 134 kb in length and encodes a variety of putative virulence-associated gene clusters, including the Vi locus, a phage encoding the SopE effector protein of PSI-1 (21-23), a type IV pilus, and a putative type IV secretion system (24)(25)(26)(27). The type IV pilus is involved in aiding attachment to eukaryotic cells (24)(25)(26)(27) and the SopE prophage harbors a gene encoding an effector protein secreted through the TTSS (14).…”
Section: Molecular and Biologic Features Of Salmonella Typhimentioning
confidence: 99%
“…Another important island is the SPI-7 which is responsible for the production of the Vi polysaccharide capsule (20). This island is 134 kb in length and encodes a variety of putative virulence-associated gene clusters, including the Vi locus, a phage encoding the SopE effector protein of PSI-1 (21-23), a type IV pilus, and a putative type IV secretion system (24)(25)(26)(27). The type IV pilus is involved in aiding attachment to eukaryotic cells (24)(25)(26)(27) and the SopE prophage harbors a gene encoding an effector protein secreted through the TTSS (14).…”
Section: Molecular and Biologic Features Of Salmonella Typhimentioning
confidence: 99%
“…It was observed that when mutations are introduced to the gene that encodes the pili (pilS) in S. typhi, their ability to adhere and invade human gastrointestinal epithelial cells in vitro was drastically reduced. [26] This suggests that the structural protein PilS may have important roles in the pathogenesis of S. Typhi in humans. Pan and coworkers have recently reported the generation of RNA aptamers against the type IVB pili of S. Typhi, which is composed largely of polymerized PilS protein.…”
Section: Salmonella Typhimentioning
confidence: 99%
“…The pili have a diameter of 6nm, as observed from an overexpressing construct under electron microscopy [43], and are expressed primarily during stationary phase in liquid culture [44].…”
Section: Type Ivb Pilus Productionmentioning
confidence: 99%
“…SPI-7 carries an operon responsible for the production of type IVB pili (pilL-pilV; STY4539-STY4550) [43]. The pili have a diameter of 6nm, as observed from an overexpressing construct under electron microscopy [43], and are expressed primarily during stationary phase in liquid culture [44].…”
Section: Type Ivb Pilus Productionmentioning
confidence: 99%
See 1 more Smart Citation